Computer applications in libraries and information centers in Metro Manila and librarian`s attitude toward computerization a survey - Lou Delong; Pascua-Cruz, Ma. Divina A.; Esquejo, Nemesio A. (1986)
This survey looks into the status of computer applications in the libraries and information centers in Metro Manila and the librarians' attitude toward computerization. Two hundred and twenty three libraries and information centers surveyed, which described the current status and the potentials of computer applications in libraries and information centers in Metro Manila as well as 74 professional librarians' attitudes toward library automation.
Three questionnaires and one structured interview schedule as well as letters, on-site visits, and telephone calls were used to collect the requisite data. Statistical methods, such as frequency distribution, mean and analysis of variance were used to present and analyze the data.
The study revealed that 29 libraries in Metro Manila have developed or have been using computerized systems in their libraries while 55 libraries are planning to utilize computerized systems in their libraries. Most of the computerized systems use IBM PC microcomputers and dBASE II or dBASE III softwares.
Within one or two years, the present number of libraries using computers may double. However the main factors affecting the implementation of the library automation plans are financial and personnel problems.
The top three priority library functions which are currently computerized are retrospective search, reference, and indexing; and the top three priority library functions which will be computerized are cataloging, indexing, and circulation.
More than 40 percent of the professional librarians have never taken any course in computer science, but no one has a negative attitude toward computer applications. Sex, age, and educational attainment are not factors affecting the librarians' attitude toward computer applications.
It is concluded that computer applications in libraries and information centers in the Philippines is only at its initial stage, but the general trend is computerization. Microcomputer is the most popular type of computer used and retrospective search, reference and indexing are the top three priority library functions computerized. On the librarians' side, they generally have a positive attitude toward the use of computers in their library operations.
Mimeographed.
Thesis (M.L.S.)--University of the Philippines, Diliman
Keywords: Information centers -- Automation. -- Philippines -- Metro Manila; Librarians -- Attitudes. -- Philippines -- Metro Manila; Libraries -- Automation. -- Philippines -- Metro Manila